The Portuguese Version of the Depressive Experiences Questionnaire (DEQ): Results from a Validation Program in Clinical and non Clinical Samples - Campos, Rui C. (2014)
The Depressive Experiences Questionnaire (DEQ, Blatt, D’Afflitti, & Quinlan, 1976, 1979), a self-report measure used in personality research, assesses the constructs of Dependency and Self-Criticism as vulnerability factors in depression (Blatt, 1974, 1990, 2004) and psychopathology more generally (Blatt, 2008; Blatt & Shichman, 1983). This study establishes a Portuguese version of the DEQ with six samples: a bilingual sample to test the measurement equivalence of the Portuguese DEQ, and two college student samples, two community samples and a clinical sample, to test the reliability, factor structure and criterion, convergent and predictive validity of this translation of the DEQ. A measure of depression (Center for Epidemiologic Studies Depression Scale; CES-D; Radloff, 1977) and of general psychopathology (Brief Symptom Inventory; BSI; Derogatis, 1993) evaluated the convergent validity of the DEQ. Findings indicate satisfactory reliability and validity of the Portuguese DEQ, and the value of the DEQ for investigating the relationship between personality and depression and between personality and psychopathology more generally. It is important to note, however, that these conclusions are based on a limited clinical sample. Additional reliability and validity data are needed with a larger clinical sample.